Answer:
1638
Step-by-step explanation:
3(500)+3(40)+3(6)=1500+120+18=1638
3.option a (-8,2)
4.option b (5,4)
19, cuz 4x19 is 76 and 72<76
I'm guessing the second derivative is for <em>y</em> with respect to <em>x</em>, i.e.
![\dfrac{\mathrm d^2y}{\mathrm dx^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%5E2y%7D%7B%5Cmathrm%20dx%5E2%7D)
Compute the first derivative. By the chain rule,
![\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\mathrm dy}{\mathrm d\theta}\dfrac{\mathrm d\theta}{\mathrm dx}=\dfrac{\frac{\mathrm dy}{\mathrm d\theta}}{\frac{\mathrm dx}{\mathrm d\theta}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20d%5Ctheta%7D%5Cdfrac%7B%5Cmathrm%20d%5Ctheta%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B%5Cfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20d%5Ctheta%7D%7D%7B%5Cfrac%7B%5Cmathrm%20dx%7D%7B%5Cmathrm%20d%5Ctheta%7D%7D)
We have
![y=b\sin\theta\implies\dfrac{\mathrm dy}{\mathrm d\theta}=b\cos\theta](https://tex.z-dn.net/?f=y%3Db%5Csin%5Ctheta%5Cimplies%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20d%5Ctheta%7D%3Db%5Ccos%5Ctheta)
![x=a\cos\theta\implies\dfrac{\mathrm dx}{\mathrm d\theta}=-a\sin\theta](https://tex.z-dn.net/?f=x%3Da%5Ccos%5Ctheta%5Cimplies%5Cdfrac%7B%5Cmathrm%20dx%7D%7B%5Cmathrm%20d%5Ctheta%7D%3D-a%5Csin%5Ctheta)
and so
![\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{b\cos\theta}{-a\sin\theta}=-\dfrac ba\cot\theta](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7Bb%5Ccos%5Ctheta%7D%7B-a%5Csin%5Ctheta%7D%3D-%5Cdfrac%20ba%5Ccot%5Ctheta)
Now compute the second derivative. Notice that
is a function of
; so denote it by
. Then
![\dfrac{\mathrm d^2y}{\mathrm dx^2}=\dfrac{\mathrm df}{\mathrm dx}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%5E2y%7D%7B%5Cmathrm%20dx%5E2%7D%3D%5Cdfrac%7B%5Cmathrm%20df%7D%7B%5Cmathrm%20dx%7D)
By the chain rule,
![\dfrac{\mathrm d^2y}{\mathrm dx^2}=\dfrac{\mathrm df}{\mathrm d\theta}\dfrac{\mathrm d\theta}{\mathrm dx}=\dfrac{\frac{\mathrm df}{\mathrm d\theta}}{\frac{\mathrm dx}{\mathrm d\theta}}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%5E2y%7D%7B%5Cmathrm%20dx%5E2%7D%3D%5Cdfrac%7B%5Cmathrm%20df%7D%7B%5Cmathrm%20d%5Ctheta%7D%5Cdfrac%7B%5Cmathrm%20d%5Ctheta%7D%7B%5Cmathrm%20dx%7D%3D%5Cdfrac%7B%5Cfrac%7B%5Cmathrm%20df%7D%7B%5Cmathrm%20d%5Ctheta%7D%7D%7B%5Cfrac%7B%5Cmathrm%20dx%7D%7B%5Cmathrm%20d%5Ctheta%7D%7D)
We have
![f=-\dfrac ba\cot\theta\implies\dfrac{\mathrm df}{\mathrm d\theta}=\dfrac ba\csc^2\theta](https://tex.z-dn.net/?f=f%3D-%5Cdfrac%20ba%5Ccot%5Ctheta%5Cimplies%5Cdfrac%7B%5Cmathrm%20df%7D%7B%5Cmathrm%20d%5Ctheta%7D%3D%5Cdfrac%20ba%5Ccsc%5E2%5Ctheta)
and so the second derivative is
![\dfrac{\mathrm d^2y}{\mathrm dx^2}=\dfrac{\frac ba\csc^2\theta}{-a\sin\theta}=-\dfrac b{a^2}\csc^3\theta](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20d%5E2y%7D%7B%5Cmathrm%20dx%5E2%7D%3D%5Cdfrac%7B%5Cfrac%20ba%5Ccsc%5E2%5Ctheta%7D%7B-a%5Csin%5Ctheta%7D%3D-%5Cdfrac%20b%7Ba%5E2%7D%5Ccsc%5E3%5Ctheta)
Angle D and angle B are equal.